Famine and food insecurity in Ethiopia - von Braun, Joachim; Olofinbiyi, Tolulope (Cornell University, 2007)
Ethiopia, the second most populous country in Sub-Saharan Africa, is home to about 75 million people. The country has a tropical monsoon climate characterized by wide topographic-induced variations. With rainfall highly erratic, Ethiopia is usually at a high risk for droughts as well as intraseasonal dry spells. The majority of the population depends on agriculture as the primary source of livelihood, and the sector is dominated by smallholder agriculture. These small farmers rely on traditional technologies and produce primarily for consumption. Famine vulnerability is high in Ethiopia. With the rapid population growth of the past two decades, per capita food grain production has declined. Cereals constitute the largest share of food production in the country. Today, with recurrent famine threats, food aid is an important source of cereal supply. Additionally, agricultural market dysfunctions are common in Ethiopia. Throughout history, the state has controlled the markets. With the enactment of a major market reform in the 1990s, the country saw some progress. Markets remain thin, however, with wide price spreads and volatility. In 2002, despite good harvests in the previous years, Ethiopia was hit by another famine: Production was insufficient, and food did not flow from surplus to deficit areas. Apart from population pressure, the causes of this crisis include production, market, policy, institutional, and organizational failures. Each time a food crisis occurs, there is a complex interaction of supply, distribution, and demand factors. It is these processes at work on national and household levels that determine outcomes for food security, food availability, access, and use. Because the causes of famine are multifaceted, multiple actions are required to prevent its occurrence. On a broader level, two points must be emphasized. First, specific programs alone cannot effectively tackle famine. Micro-level interventions should be considered in tandem with macroeconomic policies. Second, market integration and price stabilization must be in place for individual projects to function effectively. The question of policy and program choice and sequencing arise in determining the optimal program mix for mitigating and preventing famine. But how is such a program mix determined under resource and time constraints? Your assignment is to recommend a set of shortand long-term policies and programs to improve food security in Ethiopia that will be compatible with available government resources and reductions of Ethiopia’s dependence on foreign food aid.